2013
DOI: 10.1248/bpb.b12-00947
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin But Not Quercitrin Ameliorates Tumor Necrosis Factor-Alpha-Induced Insulin Resistance in C2C12 Skeletal Muscle Cells

Abstract: Skeletal muscle is a major site for glucose metabolism and its injury by cytokines can induce insulin resistance leading to type 2 diabetes. It has been suggested that quercetin may act as an anti-diabetic agent, however, the effects of quercetin on insulin resistance in skeletal muscle remain unknown. We aimed to investigate the role of quercetin and its glycoside, quercitrin in tumor necrosis factor-alpha (TNF-α) induced C2C12 skeletal muscle cell impairment. Quercetin, but not quercitrin moderately attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
2
26
2
Order By: Relevance
“…Taken together, these data suggested that ClEtOH probably has compounds that, isolated or combination, present an insulin-like action, stimulating insulinsignalling intermediates. Corroborating our hypothesis, Dai et al (2013) attributed the antidiabetic effect of quercetin to its ability to stimulate AKT (and also AMPK) in skeletal muscle cells, leading to an increased glucose uptake. Finally, the stimulation of hepatic AKT could explain not only the decrease in the PEPCK levels and in gluconeogenesis but also the increase in the hepatic glycogen content previously observed in diabetic rats treated with ClEtOH (Dechandt et al 2013); the stimulation of liver glycogen synthesis could be an additional mechanism of the extract that also contributes to reduce hyperglycaemia.…”
Section: Discussionsupporting
confidence: 62%
“…Taken together, these data suggested that ClEtOH probably has compounds that, isolated or combination, present an insulin-like action, stimulating insulinsignalling intermediates. Corroborating our hypothesis, Dai et al (2013) attributed the antidiabetic effect of quercetin to its ability to stimulate AKT (and also AMPK) in skeletal muscle cells, leading to an increased glucose uptake. Finally, the stimulation of hepatic AKT could explain not only the decrease in the PEPCK levels and in gluconeogenesis but also the increase in the hepatic glycogen content previously observed in diabetic rats treated with ClEtOH (Dechandt et al 2013); the stimulation of liver glycogen synthesis could be an additional mechanism of the extract that also contributes to reduce hyperglycaemia.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to this, quercetin treatments resulted in interesting effects, improving insulin sensitivity in muscle cells through the AMPK pathway, which is involved in cellular glucose uptake by glucose transporter type 4. These findings suggest that quercetin constitutes a nutraceutical compound able to ameliorate insulin resistance in muscle cells through different events linked to AMPK phosphorylation and activation [87]. Phenolic alcohols, such as hydroxytyroxol (Table 3) were also found to increase fatty acid oxidation and to improve insulin sensitivity through AMPK phosphorylation, as shown in 3T3-L1 adipocytes, suggesting its possible involvement in diabetes mellitus management [88].…”
Section: Nutraceutical Compounds and Type II Diabetes Mellitusmentioning
confidence: 99%
“…Furthermore, quercetin alleviates AS development in rabbits (30) and mice (31). Quercetin has also been demonstrated to control blood glucose levels, and improve glucose uptake and insulin sensitivity in vitro (32,33). Suganya et al (34) also demonstrated that quercetin prevents tunicamycin-induced ER stress through modulation of GRP78 and CHOP levels in endothelial cells.…”
Section: Introductionmentioning
confidence: 98%